Isoalantolactone Increases the Sensitivity of Prostate Cancer Cells to Cisplatin Treatment by Inducing Oxidative Stress - Huang, Hang; Li, Ping; Ye, Xueting; Zhang, Fangyi; Lin, Qi; Wu, Keming; Chen, Wei (Frontiers in Cell and Developmental Biology, 2021)
Prostate cancer is the most common malignancy among men worldwide. Platinum (II)-based chemotherapy have been used to treat a number of malignancies including prostate cancer. However, the potential of cisplatin for treating prostate cancer is restricted owing to its limited efficacy and toxic side effects. Combination therapies have been proposed to increase efficacy and reduce toxic side effects. In the present study, we investigated how isoalantolactone (IATL), a sesquiterpene lactone extracted from the medicinal plant Inula helenium L, acts synergistically with cisplatin on human prostate cancer cells. We show that IATL significantly increased cisplatin-induced growth suppression and apoptosis in human prostate cancer cells. Mechanistically, the combined treatment resulted in an excessive accumulation of intracellular reactive oxygen species (ROS), which leads to activation of endoplasmic reticulum (ER) stress and JNK signaling pathway in human prostate cancer cells. Pretreatment of cells with the ROS scavenger N-acetylcysteine (NAC) significantly abrogated the combined treatment-induced ROS accumulation and cell apoptosis. In addition, the activation of ER stress and JNK signaling pathway prompted by IATL and cisplatin was also reversed by NAC pretreatment. In vivo, we found that IATL combined with cisplatin showed the strongest anti-tumor effects compared with single agents. These results support the notion that IATL and cisplatin combinational treatment may be more effective for treating prostate cancer than cisplatin alone.